Incorporating Fatty Acids Enhanced the Performance of Konjac Glucomannan/Chitosan/Zein Film - Xiumei Wang; Yibin Chen; Xiaoxu Zhao; Jie Pang (Foods)
The effects of stearic acid (SA) and lauric acid (LA) with different concentrations on the structure and physicochemical properties of konjac glucomannan (KGM)/chitosan (CTS)/Zein (KCZ) film were systematically investigated in this paper. The rheology results suggested that the apparent viscosity of the KCZ film solution was significantly enhanced after adding fatty acids (FAs), and all the film-forming solutions were typical non-Newtonian pseudoplastic fluids. Hydrogen bond interactions were formed among KGM, CTS, Zein, and FA molecules. KCZ-FA films had higher crystallinities than KCZ film, and their crystallinities increased with the increase in FA concentrations. Microstructure indicated that adding FAs significantly affected the surface morphologies and roughness of KCZ film. KCZ-LA films exhibited much rougher surfaces than KCZ-SA films when FA concentrations were the same. Moreover, the incorporation of FAs significantly (p < 0.05) decreased the transmittance of KCZ film. KCZ-FA films exhibited higher hydrophobicities and water vapor barrier properties than KCZ film due to their significantly (p < 0.05) higher water contact angle, lower water solubility, water content, and vapor permeability values. The thermal stabilities, color attributes, and mechanical properties of KCZ film were also improved after adding appropriate concentrations of FA. Therefore, KCZ-FA films with excellent performances are promising food packaging materials in the future.